الوسيط القضائي في ظل قانون الإجراءات المدنية والإدارية الجزائري - حسون, محمد علي; حملاوي, نجاة (Revue jurisprudence, 2018)
تعتبر الوساطة من الطرق البديلة لفض المنازعات، وقد عرفتها البشرية منذ القدم وتبناها الفقه الإسلامي بعد أن عدل إجراءاتها، وتطورت إلى أن أصبحت في وقتنا الحالي أمرا ملحا تلبية لمتطلبات التطور في التقاضي الذي عرفه العصر الحديث، والذي أصبحت فيه المحاكم تعج بكثرة المنازعات والتي عجزت عن التصدي لها . وقد عالج المشرع الجزائري في القانون رقم 08-09 المؤرخ في 25 /04/2008 المتضمن قانون الإجراءات المدنية والإدارية موضوع الوساطة التي تقوم على الحوار والتفاوض بين الأطراف المتنازعة من خلال شخص ثالث محايد يسمى الوسيط . إن مهمة الوسيط الأساسية تكمن في إيجاد حل يلاءم طرفي النزاع، وفي ذلك ما يشبه نظام محافظ الدولة، إلا أن الوسيط لا يحمل صفة قاض، فهو يمارس عملا استثنائيا بديلا لعمل القاضي لفض النزاع، من خلال استدعاء الخصوم لحضور جلسات الوساطة في سرية تامة ليستمع إلى أقوالهم وذلك قبل انعقاد جلسة المحاكمة . و تهدف هذه الدراسة إلى تغطية الجوانب الإجرائية لنظام الوساطة كأحد الحلول البديلة لتسوية النزاعات المدنية والإدارية وفقا للقانون الجزائري لإبراز مدى تكفل المشرع بهذا النظام . الكلمات المفتاحية : الوساطة، الطرق البديلة، فض النزاعات، الوسيط . Abstract: Mediation is one of the alternative methods for disputes settlement. It was known since ancient times by humanity and adopted in Islamic jurisprudence after some modifications. It has evolved to become an urgent necessity in the present time, to meet the evolved requirements of litigating in which the courts become unable to handle it. Under the law no. 08/09 of 25/04/2008 including the Civil and Administrative Act, the Algerian legislator treated the subject of mediation which is based on dialogue and negotiation between parties of the conflict through a neutral third person called the mediator. Mediator’s main task is to find a solution that suits the two parties to the conflict, which is similar to Commissioner of State system. However, the mediator does not have judge status, but he performs an exceptional job as an alternative to the judge’s job in resolving disputes by summoning the litigants to attend to the mediation sessions secretly before the trial session. This study aims to cover the procedural aspects of the mediation system as an alternative solution to resolve civil and administrative disputes in accordance with the Algerian law, in the aim of highlighting how far the legislator ensured this system. Keywords: Mediation, alternative methods, disputes settlement, negotiation.